2013
DOI: 10.1002/cbf.2976
|View full text |Cite
|
Sign up to set email alerts
|

In non‐small cell lung cancer mitogenic signaling leaves Sprouty1 protein levels unaffected

Abstract: Sprouty1 protein belongs to a family of receptor tyrosine kinase-mediated signaling inhibitors, whose members are usually regulated by growth factors to form a negative feedback loop. Correspondingly fluctuations of Sprouty1 mRNA in response to single growth factors have been observed. In this report, we investigate Sprouty1 protein levels and show that in non-small cell lung carcinoma-derived cells, the expression levels are unaffected by the serum content in the cellular environment. Although cells harboring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Protein isolation and immunoblotting were carried out as described [ 26 ]. Spry-specific antibodies were produced earlier [ 23 , 26 , 27 ] as described [ 27 ]. Antibodies recognizing PDCD4 (monoclonal, rabbit antibody EPR3431 from Epitomics was diluted 1:5000) and PTEN (monoclonal rabbit antibody EPR4408 from Epitomics was diluted 1:1000) were purchased.…”
Section: Methodsmentioning
confidence: 99%
“…Protein isolation and immunoblotting were carried out as described [ 26 ]. Spry-specific antibodies were produced earlier [ 23 , 26 , 27 ] as described [ 27 ]. Antibodies recognizing PDCD4 (monoclonal, rabbit antibody EPR3431 from Epitomics was diluted 1:5000) and PTEN (monoclonal rabbit antibody EPR4408 from Epitomics was diluted 1:1000) were purchased.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting was carried out as described [23] using affinity purified antibodies against the NH 2 ‐terminus of Spry2 (characterised in [16]) and Spry4 (described in [24]). As a loading control primary antibodies against β‐actin (Novus Biologicals) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Parallel studies consistently reported that the expression of Spry2 and Spry4 was rapidly induced by growth factors in fibroblasts [5], endothelial cells [6], and HEK293 cells [60], yet concomitant downregulation of Spry1 was observed [5, 6]. Moreover, Kral et al [79] demonstrated that neither growth factor stimulation nor Ras activation increased the Spry1 protein levels in WI38 normal human lung fibroblasts. Since Spry1 in their cell cycle analysis with WI38 cells was constantly expressed, they concluded that mitogenic signaling is not sufficient to modulate the Spry1 expression, and that Spry1, as appeared in earlier studies [19, 80, 81], is more likely modulated by differentiation processes.…”
Section: Sprouty: a Versatile Modulator With Complex Functionalitymentioning
confidence: 95%